Effect of UBE2L3 genotype on regulation of the linear ubiquitin chain assembly complex in systemic lupus erythematosus. (26th February 2015) - Lewis, Myles; Vyse, Simon; Shields, Adrian; Boeltz, Sebastian; Gordon, Patrick; Spector, Timothy; Lehner, Paul; Walczak, Henning; Vyse, Timothy
Abstract: Background: A single risk haplotype across UBE2L3 is strongly associated with systemic lupus erythematosus (SLE) and many other autoimmune diseases. UBE2L3 is an E2 ubiquitin-conjugating enzyme with specificity for RING-in-between-RING E3 ligases, including HOIL-1 and HOIP, components of the linear ubiquitin chain assembly complex (LUBAC), which has a pivotal role in inflammation, through crucial regulation of NF-κB. We aimed to determine whether UBE2L3 regulates LUBAC-mediated activation of NF-κB, and determine the effect of UBE2L3 genotype on NF-κB activation and B-cell differentiation. Methods: UBE2L3 genotype data from SLE genome-wide association studies was imputed by use of 1000 Genomes data. UBE2L3 function was studied in a HEK293-NF-κB reporter cell line with standard molecular biology techniques. p65 NF-κB translocation in ex-vivo B cells and monocytes from genotyped healthy individuals was quantified by imaging flow cytometry. B-cell subsets from healthy individuals and patients with SLE, stratified by UBE2L3 genotype, were determined by multicolour flow cytometry. Findings: rs140490, located at −270 base pairs of the UBE2L3 promoter, was identified as the most strongly associated single nucleotide polymorphism (p=8·6 × 10 −14, odds ratio 1·30, 95% CI 1·21–1·39). The rs140490 risk allele increased UBE2L3 expression in B cells and monocytes. Marked upregulation of NF-κB was observed with combined overexpression of UBE2L3 and LUBAC, but abolished by dominant-negative mutant UBE2L3 (C86S), or UBE2L3 silencing. The rs140490 genotype correlated with basal NF-κB activation in ex-vivo human B cells and monocytes, as well as NF-κB sensitivity to CD40 or tumour necrosis factor (TNF) stimulation. UBE2L3 expression was 3–4 times higher in circulating plasmablasts and plasma cells than in other B-cell subsets, with higher levels in patients with SLE than in controls. The rs140490 genotype correlated with increasing plasmablast and plasma cell differentiation in patients with SLE. Interpretation: This study shows that NF-κB activation mediated by LUBAC is exquisitely sensitive to the expression level of UBE2L3 . The UBE2L3 risk haplotype is correlated with TNF and CD40 induced NF-κB activation in primary human cells, and with plasmablast and plasma cell expansion in SLE, consistent with the dependence of these cells on NF-κB as a survival factor. Since UBE2L3 is highly expressed in plasma cells, UBE2L3 could be a novel therapeutic target in SLE. Funding: Arthritis Research UK, Wellcome Trust, George Koukis Foundation, European Community's Seventh Framework Programme.